Humanism, Racial Perceptions and Identity Development in an Adult Classroom Setting: An Empirical Study - Rose Borunda; Carissa Brehm; Courtenay Tessler; Nancy Padrick (Adult Education Research Conference, 2010)
This qualitative study provides outcome data that documents shifts in self identity and in cross racial perceptions when historical and modern day white humanist Euro-American models are introduced to students in two pre-graduate level classes. Classroom facilitation about the models and their work provided positive archetypes to counter capitalist images that have traditionally been touted as this nation’s “heroes.”